2017
DOI: 10.1007/s13238-017-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

Salivary exosomal PSMA7: a promising biomarker of inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is an intestinal immune-dysfunctional disease worldwide whose prevalence increasing in Asia including China. It is a chronic disease of the gastrointestinal tract with unknown cause. Exosomes are small vesicles in various body fluids. They have diameters of 40–120 nm, and one of their functions is long-distance transfer of various substances. In this study, we investigated the contents of salivary exosomes in patients with IBD and in healthy controls to explore a new biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 26 publications
(27 reference statements)
1
78
0
1
Order By: Relevance
“…The pathogenesis of IBD is extremely complex, involving multiple pathways and cytokines. 22,23 The disease is unpredictable and incurable. 24 Therefore, understanding the mechanism underlying IBD would be helpful in finding the best treatment options as early as possible, which would improve long-term treatment results and quality of life in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of IBD is extremely complex, involving multiple pathways and cytokines. 22,23 The disease is unpredictable and incurable. 24 Therefore, understanding the mechanism underlying IBD would be helpful in finding the best treatment options as early as possible, which would improve long-term treatment results and quality of life in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating pathogenesis-related EVs have emerged as promising biomarkers to monitor disease development and as novel targets for future anti-inflammation therapies in IBD. In 2017, Zheng et al investigated the high sensibility of salivary exosomal PSMA7 on IBD diagnosis [121]. This study identified the proteins within EVs by using a liquid chromatograph-mass spectrometer, and PSMA7 was shown to be associated with inflammation and immune response as well as depressive disorder in many studies [122,123].…”
Section: Clinical Potential Of Evs As Biomarkersmentioning
confidence: 99%
“…Because of the involvement of exosomes in modulation of immune cells and disease progression, differentially expressed exosomal proteins have been proposed as biomarkers for IBD. LC–MS and bioinformatic analysis of exosomes from saliva samples of IBD patients versus healthy controls identified proteasome subunit alpha type 7 (PSMA7), a protein related to proteasome activity and the inflammatory response, as significantly upregulated in IBD patients . The potential for IBD screening via bodily fluids such as saliva provides a much less invasive alternative to colonoscopy.…”
Section: Role Of Exosomesmentioning
confidence: 99%